Undernutrition and its association with socio-demographic factors among pregnant women attending tertiary health care hospital in northern Maharashtra: a cross sectional study - Rathod, Mamta S.; Borde, Anant N.; Patil, Sarika P.; Bawa, Mukesh S.; Gosavi, Shriram; Pagar, Vikrant; Kinge, Amol; Chavan, Sushant (International Journal Of Community Medicine And Public Health, 2019)
Background: Maternal nutrition is one of the most important health and welfare problems among women in developing countries. Only limited research has been conducted on the prevalence and determinants of maternal nutritional status in Maharashtra. Particularly, data on the nutritional status of pregnant women are lacking. The aim of this was to assess prevalence and determinants of undernutrition among pregnant women attending antenatal care center. Methods: An institution based cross-sectional study was conducted during September to December, 2018. Randomly selected 303 pregnant women were included in the study. Nutritional status was estimated using mid-upper-arm circumference. Data on potential determinants of undernutrition were gathered using a structured questionnaire. Statistical analysis was done using logistic regression. p<0.05 at 95% confidence interval was considered as statistically significant. Results: Overall prevalence of under-nutrition among study participants was 21.8%. Using a logistic regression model, factors significantly associated with the under nutrition were rural residence (AOR=0.675; 95%CI 0.307-1.485), having less than three years duration of marriage (AOR=6.650;95%CI 2.268-19.501), living with joint family (AOR=4.128;95%CI 1.606-10.611), no utilization of family planning methods (AOR=0.319; 95%CI 0.131-0.775), less no. of ANC visit (AOR=3.253; 95%CI 1.342-7.888) and having less frequency of meal (AOR=0.319 (0.149-0.683). Remaining all factors like religion, education, occupation, family size, gravida, parity, consumption of iron and calcium tablet, getting USG done, anti-tetanus vaccination, support from family and husband were not found as significant risk factors for undernutrition. Conclusions: Integrated approach is must to combat malnutrition among pregnant women.